Discussion of “The New Role of Biomedical Informatics in the Age of Digital Medicine” - Al-Shorbaji, Najeeb; Bellazzi, Riccardo; de Quiros, Fernan Gonzalez Bernaldo; Koch, Sabine; Kulikowski, Casimir A.; Lovell, Nigel H.; Maojo, Victor; Park, Hyeoun-Ae; Sanz, Ferran; Sarkar, Indra N.; Tanaka, Hiroshi (Methods of Information in Medicine, 2016)
This article is part of a For-Discussion-Section of Methods of Information in Medicine about the paper “The New Role of Biomedical Informatics in the Age of Digital Medicine” written by Fernando J. Martin-Sanchez and Guillermo H. Lopez-Campos [1]. It is introduced by an editorial. This article contains the combined commentaries invited to in -dependently comment on the paper of Martin-Sanchez and Lopez-Campos. In subsequent issues the discussion can continue through letters to the editor.
Keywords: Biomedical informatics; digital medicine; participatory medicine; precision medicine; social media; self-quantification; exposome